The requirement of glycoprotein C (gC) for interindividual spread is a conserved function of gC for avian herpesviruses - Widaliz Vega-Rodriguez (Nature Portfolio, 2021)
Abstract We have formerly shown that glycoprotein C (gC) of Gallid alphaherpesvirus 2, better known as Marek’s disease (MD) alphaherpesvirus (MDV), is required for interindividual spread in chickens. Since gC is conserved within the Alphaherpesvirinae subfamily, we hypothesized gC was important for interindividual spread of other alphaherpesviruses. To test this hypothesis, we first generated a fluorescent protein tagged clone of Gallid alphaherpesvirus 3 MD vaccine strain 301B/1 to track virus replication in cell culture and chickens using fluorescent microscopy. Following validation of this system, we removed the open reading frame of 301B/1 gC from the genome and determined whether it was required for interindividual spread using experimental and natural infection studies. Interindividual spread of MD vaccine 301B/1 was abrogated by removal of 301B/1 gC. Rescuent virus in which 301B/1 gC was inserted back into the genome efficiently spread among chickens. To further study the conserved function of gC, we replaced 301B/1 gC with MDV gC and this virus also efficiently spread in chickens. These data suggest the essential function of alphaherpesvirus gC proteins is conserved and can be exploited during the generation of future vaccines against MD that affects the poultry industry worldwide.